KAILAN (Brassica oleraceae var acephala) GROWTH AND YIELD AT CONCENTRATIONS OF PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) AND OTHER PLANTING MEDIA ONE OF THE TEHNIC EMPOWERMENT FARMERS: Kailan, planting media, PGPR. - hadi, pramono hadi; Rahayu, Tri; Al Fatonah, Fatma (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
ABSTRACK The study was titled Kailan (Brassica oleraceae var acephala) Growth And Yield at Concentration of Plant Growth Promotion Rhizobacteria (PGPR) And Other Planting Media One of The Tehnic Empowerment Farmers. It has been held in November 2019 until January 2020 in Kondo Hamlet, Balong Village, Jenawi District, Karanganyar Regency. This study uses a Complete Randomized Design (RAL) method consisting of 2 treatment factors first is a kind of planted media (M) consists of 3 kinds, namely: soil media, straw compost and goat manure (M1), soil media straw compost and cow manure (M2), soil media, straw compost and chicken manure (M3) . The second factor is the concentration of PGPR (K) consisting of 3 treatment concentrations of PGPR 0 ml / l water (K0), PGPR concentration of 15 ml / l of water (K1), concentration of PGPR 30m l / l of water (K2). The results showed that the variety of planting media has a very different effect on the number of leaves, the weight of wet clusters, and has a real effect on the weight of consumption and volume of leaves and has no real effect on the height of plants. PGPR concentration treatment is very influential on leaf volume, has a real effect on leaf count, consumption weight, high plant, but has no noticeable effect on wet trapping weight. Interaction of various planting media and PGPR concentration shows no noticeable effect on the number of leaves per plant, consumption weight, wet weight, height of plants and leaf volume. The variety of planted media and PGPR concentration to the growth and yield of kailan plants is shown in the parameters of heavy wet weight consumption weight (46.97 g) obtained in the combination of treatment M2K1 (mixed media soil, straw compost and manure cattle, with a concentration of PGPR 15 ml / l water). The weight of the slimmest consumption (21.15 g), obtained in the combination of M1K0 treatment (mixed media of soil, straw compost and goat manure, with a PGPR concentration of 0 ml / litre of water). Keywords: Kailan, planting media, PGPR.